2014
DOI: 10.1175/jcli-d-13-00393.1
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Effect on Trends of Extreme Temperature Indices of National Stations over Mainland China, 1961–2008

Abstract: Understanding the long-term change of extreme temperature events is important to the detection and attribution of climate change. It is unclear, however, how much effect urbanization has had on trends of the extreme temperature indices series constructed based on the commonly used datasets on a subcontinental scale. Applying a homogenized daily temperature dataset of the national reference climate stations and basic meteorological stations, and a rural station network previously developed, urbanization effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
244
5
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(263 citation statements)
references
References 40 publications
12
244
5
2
Order By: Relevance
“…We anticipate that aerosols can play an important role in the decrease in R n in the arid region by absorbing and scattering solar irradiance. Furthermore, additional heating due to urbanization may cause different trends in atmospheric water demands between urban and rural areas (Han et al, 2012;Ren and Zhou, 2014). However, examining the effects of LULCC and aerosols on trends in surface dryness lies beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…We anticipate that aerosols can play an important role in the decrease in R n in the arid region by absorbing and scattering solar irradiance. Furthermore, additional heating due to urbanization may cause different trends in atmospheric water demands between urban and rural areas (Han et al, 2012;Ren and Zhou, 2014). However, examining the effects of LULCC and aerosols on trends in surface dryness lies beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Artificial heat emission and land cover change near the meteorological stations are mainly the results of city expansion or urbanization. Many studies suggested that urbanization has significantly affected surface air temperature change through modifying land cover, air composition and the anthropogenic heat release (Ren et al 2008, Ren andZhou 2014;Zhou and Ren 2009;Hu et al 2010;Zhang et al 2010;Parker 2010;Stewart 2011;Li and Zhao 2012;Wang et al 2012). Ren (2009), Zhang et al (2011a) and Ren and Zhou (2014) found that the single-site and regional-scale urbanization in mainland China had more significantly increased the minimum temperature trends and significantly narrowed the DTR during the past five decades.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly increased aerosol concentrations by pollutant emission in eastern China for the last few decades have been reported (e.g., Qian et al 2009b) and have been suggested to be responsible for the observed reduction in global solar radiation (Qian et al 2007). Ren and Zhou (2014) showed that the urbanization effect significantly reduced DTR in China by comparing urban sites to rural sites, ) estimated over the entire 30-year period; those in the lower half indicate the linear trend coefficients estimated for the periods 1979-1989 and 1990-2008. * (**)Denotes that the linear trend is statistically significant at p<0.05 (0.01) which were chosen from ordinary meteorological stations based on population.…”
Section: Discussionmentioning
confidence: 99%
“…3h, which shows that the largest warming is located in North China Plain. Ren and Zhou (2014) showed that urbanization effects in China are more apparent for Tmin in North China Plain. These urbanization effects may be related mainly to the heat release from the urban infrastructure during the night.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation